The Influence of Occupational Safety and Health Programs on Employee Performance of PT. PLN (Persero) Upt Makassar - Andi Nur Rezkhy; Sitti Nurbaya; Sitti Marhumi (Yayasan Amerta Insan Unggul, 2024)
This study investigates the impact of Occupational Safety and Health (OSH) programs on employee performance at PT. PLN (Persero) UPT Makassar. Using a quantitative approach, data were collected from 56 employees through structured questionnaires and analyzed with SPSS version 29. The OSH program, encompassing workplace conditions, health services, and environmental safety, was measured as the independent variable, while employee performance, indicated by work quality, behavior, and personal attributes, served as the dependent variable. Results from descriptive and regression analyses indicate a significant positive influence of OSH programs on employee performance, with a regression coefficient of 0.761 and a coefficient of determination (R²) of 0.676. This suggests that 67.6% of variations in employee performance are explained by the OSH program. The findings underscore the importance of continuous implementation and enhancement of OSH initiatives, such as safety training and personal protective equipment usage, to improve employee productivity and maintain a safe work environment. The study contributes to organizational management practices by demonstrating that effective OSH programs are essential for achieving optimal employee performance and workplace safety.